KOMUNIKASI HIPERPERSONAL (HYPERPERSONAL COMMUNICATION) PROSES PELIPUTAN BERITA DI JAKTV MENGGUNAKAN APLIKASI ZOOM MEETING - Danil Arifaini; Afrina Sari (Program Studi Ilmu Komunikasi Fakultas Ilmu Sosial dan Ilmu Politik Universitas Baturaja, 2021)
ABSTRACT Hyperpersonal Communication (Hyperpersonal Communication) News Coverage Process in Jak Tv Using Zoom Meeting The concept of working from home (WFH) has been the subject of discussion and the theme of world studies by researchers since the last 10 years, but this global phenomenon began to emerge when Covid 19 struck and has become an alternative strategy for many organizations. The development of information technology does not only have an impact on the organization, but also has an impact on the lifestyle and social life of the community. WFH is a strategy for many organizations with all the advantages and disadvantages that the organization and its employees must accept. Zoom Meeting is used as an alternative in conducting general coverage such as press conferences, virtual discussions, interviewing sources or figures related to the news that will be broadcast by JakTv. The use of zoom can help in the process of news coverage (news presentation) by 70% even though it has limitations such as stock shoot images and its normative use is very helpful, but personally there are things that cannot be replaced from direct (face-to-face) meetings. Conceptually, the use of zoom can be said to have fulfilled the elements of hyperpersonal communication, because communication is carried out using computer mediation and even smartphones. In general, the coverage process at JakTv uses zoom including editorial meetings, determining the topic of coverage and assigning reporters to cover, and news coverage (reportage, interviews, library research and news agencies). The use of zoom during reporting on JakTv in terms of interview content has fulfilled the 5W + 1H elements, but in terms of content, stock images are difficult to get when interviewing. Keywords: Pandemic Covid 19, Work From Home, Zoom Meeting, Covering.